Establishing specialized health services for professional consultation in euthanasia: experiences in the Netherlands and Belgium - Bilsen Johan; Onwuteaka-Philipsen Bregje D; Cohen Joachim; Van Wesemael Yanna; Deliens Luc (BMC, 2009)
Abstract Background The Netherlands, Belgium, and Luxembourg have adopted laws decriminalizing euthanasia under strict conditions of prudent practice. These laws stipulate, among other things, that the attending physician should consult an independent colleague to judge whether the substantive criteria of due care have been met. In this context initiatives were taken in the Netherlands and Belgium to establish specialized services providing such consultants: Support and Consultation for Euthanasia in the Netherlands (SCEN) and Life End Information Forum (LEIF) in Belgium. The aim of this study is to describe and compare these initiatives. Methods We studied and compared relevant documents concerning the Dutch and Belgian consultation service (e.g. articles of bye-laws, inventories of activities, training books, consultation protocols). Results In both countries, the consultation services are delivered by trained physicians who can be consulted in cases of a request for euthanasia and who offer support and information to attending physicians. The context in which the two organisations were founded, as well as the way they are organised and regulated, is different in each country. By providing information on all end-of-life care matters, the Belgian LEIF seems to have a broader consultation role than the Dutch SCEN. SCEN on the other hand has a longer history, is more regulated and organised on a larger scale and receives more government funding than LEIF. The number of training hours for physicians is equal. However, SCEN-training puts more emphasis on the consultation report, whereas LEIF-training primarily emphasizes the ethical framework of end-of-life decisions. Conclusion In case of a request for euthanasia, in the Netherlands as well as in Belgium similar consultation services by independent qualified physicians have been developed. In countries where legalising physician-assisted death is being contemplated, the development of such a consultation provision could also be considered in order to safeguard the practice of euthanasia (as it can provide safeguards to adequate performance of euthanasia and assisted suicide).